Energy conservation for production of 50000 MT/A Isobutylene by using pinch analysis and effect to the plant economic - Nor Hazwani, Rosley (2010)

(untitled)
This research shows how the application of Pinch Technology can lead towards great of heat recovery and energy saving. The application of this technique enables a fundamental insight into the thermal interactions between a chemical process and the utility systems to be gained. This means that a certain reconstruction and financial investment in an existing process can considerably reduce capital cost and energy consumption. Since no studies have been done on minimizing energy consumption in Isobutylene Production Plant, there is a potential for energy conservation by using Pinch Analysis. The heat exchanger network of the isobutylene process plant has been studied and it was shows how the application of pinch technology makes it possible to reduce the demand of hot and cold utility. The objectives of this research are to find the minimum energy requirement and to observe the effect of energy conservation to production cost and plant economics. In order to achieve the objectives, there are three main analysis are practiced which are Process Flow Diagram Analysis, Pinch Analysis and Economic Analysis. As the hot and cold stream was identified from the Process Flow Diagram, the thermal data extracted and recorded in a table. The value of ΔTmin was selected between 10°C to 14 °C. Next the Composite Curve and Grand Composite Curve were constructed based to the data extracted. The analysis then continued with the design of Heat Exchanger Network (HEN) where the HEN was designed at 3 different ΔTmin values which are 10°C, 12°C and 14 °C. From HEN grid diagram analysis the minimum energy requirement can be determined and the analysis proceed with plant economic analysis that only focused to the heat exchanger and another cost that might affect after the Pinch was constructed. The results obtained from the earlier analysis are compared between the three different ΔTmin to find the optimal ΔTmin. Overall analysis results in output where the optimum ΔTmin equal to 14 °C where the total annual cost of energy and capital costs is minimized and also a payback period of within one year of plant operation.